SIMULASI CONDITION MONITORING MESIN BERBASIS IOT MENGGUNAKAN ESP32 - Adam Satria; Al Kautsar Permana; Hikari Qurrata’ain Nurhadi; Archie Farras Belmino Tyto Putra (Fakultas Teknologi Lingkungan dan Mineral - Universitas Teknologi Sumbawa, 2025)
This research develops an IoT-based machine condition monitoring system capable of real-time monitoring of machine power consumption to enhance operational efficiency and predictive maintenance in industrial settings. The system utilizes the ACS712 current sensor to detect electrical current consumed by the machine. Using the Thingspeak platform, data collected from the sensor is periodically sent to a cloud server and displayed in a dashboard format, enabling remote monitoring. The monitoring program is designed to reduce the data load on the server, with data being transmitted every 10 seconds to minimize irrelevant data redundancy. In testing, the system successfully transmitted data to the Thingspeak server stably, despite occasional connectivity disruptions between the microcontroller and server. Over a total testing duration of one hour, 100 data samples were successfully uploaded, showing an average current of 2.8 Amperes and power of 550 Watts, with an operational voltage range of 220-235 Volts. The uploaded data is not only used for monitoring machine conditions but can also be further integrated into analysis to support better data-driven decision-making in industrial environments.